Symmetry breaking for semiconductor photocatalysis - Di, Jun (2024)
Numerous strategies have been developed to tailor the photocatalytic performance of catalysts. However, do any general commonalities exist in these strategies for activity improvement? It is desirable to explore the general regularity of these strategies, thus guiding further developments in the field of photocatalysis. In this review, we propose that the key or essential nature of improved photocatalytic activity depends considerably on the symmetry breaking of the materials. The detailed contributions of symmetry breaking to the increased photocatalytic activity are intensely discussed and summarized based on the location of symmetry breaking; namely, spontaneous symmetry breaking in the material interior, localized symmetry breaking on the material surface, and external-field-induced symmetry breaking beyond the material.